STRATEGIES FOR SUCCESSFUL LEARNING IN PHYSICS (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Physics has a very important place in science. Therefore, physics education should be done carefully and effectively. As studies have repeatedly shown, classical teaching models are so ineffective in physics education that the gains at the end of the learning process are almost negligible. Therefore, physics education should be based on active learning models that have been proven to be effective and natural.